Coastal Engineering Practice : Proceedings of the 2011 Conference on Coastal Engineering Practice : August 21-24, 2011, San Diego, California - Magoon, Orville T. (American Society of Civil Engineers, 2011)
This collection contains 90 papers that focus on developing solutions to coastal engineering problems and ensuring sustainable coastal development. Papers reflect an emphasis on practical experience and actual projects rather than specific technical and scientific aspects of coastal engineering. These papers enhance the exchange of real-world experience and thus will be of interest to practicing coastal engineers. -- Provided by publisher.
Keywords: Coastal engineering -- Congresses.; Coastal engineering -- United States -- Congresses.; elektronické knihy; electronic books